2004
DOI: 10.1100/tsw.2004.84
|View full text |Cite
|
Sign up to set email alerts
|

Urologic Problems in Patients with Acquired Immunodeficiency Syndrome

Abstract: , the incidence of AIDS has finally stabilized, with approximately 15,000 cases per quarter reported. 1 While AIDS appears to involve all organ systems, the genitourinary system is both primarily and secondarily affected. This article reviews the genitourinary manifestations of the human immmunodeficiency virus (HIV) and the most current treatment options available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 85 publications
0
16
1
Order By: Relevance
“…In patients with low CD4 counts bladder areflexia and hyporeflexia is a common neurologic complication, which leads to urinary stasis, and ultimately infection. Individuals with AIDS seem to be at an augmented risk of UTI, both symptomatic and asymptomatic, in comparison with asymptomatic HIV-infected and non-HIV infected patients 8,9 . Diverse studies across the globe have reported the incidence of asymptomatic bacteriuria in HIV patients as 3.1%-to the maximum of 26%compared to an average prevalence of 0.04% in healthy population 3,9,10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with low CD4 counts bladder areflexia and hyporeflexia is a common neurologic complication, which leads to urinary stasis, and ultimately infection. Individuals with AIDS seem to be at an augmented risk of UTI, both symptomatic and asymptomatic, in comparison with asymptomatic HIV-infected and non-HIV infected patients 8,9 . Diverse studies across the globe have reported the incidence of asymptomatic bacteriuria in HIV patients as 3.1%-to the maximum of 26%compared to an average prevalence of 0.04% in healthy population 3,9,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with AIDS seem to be at an augmented risk of UTI, both symptomatic and asymptomatic, in comparison with asymptomatic HIV-infected and non-HIV infected patients 8,9 . Diverse studies across the globe have reported the incidence of asymptomatic bacteriuria in HIV patients as 3.1%-to the maximum of 26%compared to an average prevalence of 0.04% in healthy population 3,9,10,11 . The present study reports asymptomatic bacteriuria (ASB) in 5.6% of HIV positive and 1 % of HIV negative individuals with a p value of 0.0358 which parallels with the findings of OM Ibadin 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were investigated and identified as HIV reactive by serological tests was done elsewhere. All of the patients were reported ELISA positive (as per WHO strategy-II 1993) for HIV-1/HIV-2 with at least two different kits [1].…”
Section: Laboratory Diagnosis Of Hiv Infectionmentioning
confidence: 99%
“…Although, infection may be present cultures are often negative. Most AIDS patients take prophylactic antimicrobials for opportunistic infections causing pneumonia or diarrhea and this renders culture negative [1].…”
Section: Introductionmentioning
confidence: 99%